Pharmacological inhibition of the CB1 cannabinoid receptor restores abnormal brain mitochondrial CB1 receptor expression and rescues bioenergetic and cognitive defects in a female mouse model of Rett syndrome - Livia Cosentino; Chiara Urbinati; Chiara Lanzillotta; Domenico De Rasmo; Daniela Valenti; Mattia Pellas; Maria Cristina Quattrini; Fabiana Piscitelli; Magdalena Kostrzewa; Fabio Di Domenico; Donatella Pietraforte; Tiziana Bisogno; et al. (Molecular Autism, 2024)
Abstract Background Defective mitochondria and aberrant brain mitochondrial bioenergetics are consistent features in syndromic intellectual disability disorders, such as Rett syndrome (RTT), a rare neurologic disorder that severely affects mainly females carrying mutations in the X-linked MECP2 gene. A pool of CB1 cannabinoid receptors (CB1R), the primary receptor subtype of the endocannabinoid system in the brain, is located on brain mitochondrial membranes (mtCB1R), where it can locally regulate energy production, synaptic transmission and memory abilities through the inhibition of the intra-mitochondrial protein kinase A (mtPKA). In the present study, we asked whether an overactive mtCB1R-mtPKA signaling might underlie the brain mitochondrial alterations in RTT and whether its modulation by systemic administration of the CB1R inverse agonist rimonabant might improve bioenergetics and cognitive defects in mice modeling RTT. Methods Rimonabant (0.3 mg/kg/day, intraperitoneal injections) was administered daily to symptomatic female mice carrying a truncating mutation of the Mecp2 gene and its effects on brain mitochondria functionality, systemic oxidative status, and memory function were assessed. Results mtCB1R is overexpressed in the RTT mouse brain. Subchronic treatment with rimonabant normalizes mtCB1R expression in RTT mouse brains, boosts mtPKA signaling, and restores the defective brain mitochondrial bioenergetics, abnormal peripheral redox homeostasis, and impaired cognitive abilities in RTT mice. Limitations The lack of selectivity of the rimonabant treatment towards mtCB1R does not allow us to exclude that the beneficial effects exerted by the treatment in the RTT mouse model may be ascribed more broadly to the modulation of CB1R activity and distribution among intracellular compartments, rather than to a selective effect on mtCB1R-mediated signaling. The low sample size of few experiments is a further limitation that has been addressed replicating the main findings under different experimental conditions. Conclusions The present data identify mtCB1R overexpression as a novel molecular alteration in the RTT mouse brain that may underlie defective brain mitochondrial bioenergetics and cognitive dysfunction.